Applied researches and projects of Department of Geography, Faculty of Arts, University of Maribor since the year 1961 - Žiberna, Igor (Journal for Geography, 2013)
Department of Geography at the Pedagogical academy was always a part of applied researches that were oriented into human geography, agricultural geography, transformation of North-Eastern Slovenia and local geography. The emphasis was made on the study related to the issues of arable land partition, minorities in Prekmurje and the boarder issues. New staff of younger generations expanded the spectrum of applied researches to new fields: revitalization of industrial areas, spatial planning, didactics of Geography, ecoremediations, local climate and environmental protection.
Keywords: applied researches; Department of Geography; Maribor